ANALISIS KESELAMATAN DAN KESEHATAN KERJA (K3) PROSES MACHINING DAN WELDING AXLE 17” PADA LINE MACHINING AXLE P.S (STUDI KASUS PT HINO MOTORS MANUFACTURING INDONESIA) - Pratama, Ahmad Ilham; Kusnadi, Kusnadi (Jurnal Ilmiah Wahana Pendidikan, 2024)
In the production process contained in the company there are aspects that cannot escape the development of the times, namely occupational health and safety (K3). PT Hino Motors Manufacturing Indonesia is a company engaged in the automotive sector that focuses on the production and assembly of trucks and buses in Indonesia. In the data on work accident cases reported to the Ministry of Manpower through the Provincial Manpower Office for the 2019-2021 period, there were findings of work accidents originating from all 126 million workers spread across every province throughout Indonesia. According to BPJS Employment in 2021 there will be 20 cases of work accidents at PT Hino Motors Manufacturing Indonesia. Therefore, it is necessary to carry out hazard identification and hazard risk assessment. Hazard identification is carried out with the aim of knowing the hazards contained in a work process in the company, while hazard risk assessment is carried out to determine the level of influence of the hazards that occur so that they can be corrected by the company. The results showed that the highest level of risk was found in hazard findings Not using self protection in accordance with the SOP, which resulted in shortness of breath and long-term biological disease. This was caused by the residual smoke from the production process that came out of the vacuum machine and spread to the production process area and had an impact on the operator .